Le rapport au savoir en formation continue : les effets de l’inconscient chez un professeur des écoles. Une étude de cas - Matthieu Laugier; Yves Félix Montagne; Denis Loizon (Recherches en Éducation)
Based on the case study of a primary school teacher, this research questions the reasons for the non-use of knowledge transmitted in swimming training courses in continuing education. Part of a clinical approach with a psychoanalytic orientation, this research explores the effects of how the unconscious operates as the thread of knowledge is being interrupted. Conducting clinical research interviews linked to the filmed observation of a swimming session allowed the collection of data.The interpretative analysis of the subject's speech reveals several unconscious manifestations for the non-use of knowledge related to the concepts of « Real », « enjoyment » and « already there ». This suggests a peculiar relation to personal knowledge which creates professional perspectives aiming at the elaboration of a teacher trainer's clinical stance.